2010
DOI: 10.2147/ndt.s9279
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone effects on [3H]-paroxetine and α2-adrenoreceptors in platelets of patients with major depression

Abstract: Trazodone is an antidepressant which behaves as a selective 5-HT2 antagonist and 5-HT reuptake inhibitor. The lack of information on its effects in vivo prompted us to evaluate α2-adrenoceptors by means of the specific binding of [3H]-rauwolscine, and the 5-HT transporter (SERT) by means of the binding of [3H]-paroxetine ([3H]-Par), in platelets of depressed patients, before and after one month of treatment with trazodone (75–300 mg/day). Twenty-five outpatients of both sexes with a diagnosis of major depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…3 Although it is widely used due to its lower anticholinergic properties and cardiac adverse effects compared to tricyclic antidepressants, and cardiac adverse effects than tricyclic antidepressants, the results of limited clinical studies investigating cardiovascular adverse effects of TRZ are conflicting. 4 It has been noted that TRZ may cause possible cardiovascular adverse effects because of the increased number of cardiotoxicity reports associated with TRZ treatment over the past years. 5,6 Studies have shown that postural hypotension, electrocardiogram (ECG) anomalies (such as prolonged PR interval, long QT syndrome), and cardiac arrhythmias were induced at therapeutic and subtherapeutic doses of TRZ.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although it is widely used due to its lower anticholinergic properties and cardiac adverse effects compared to tricyclic antidepressants, and cardiac adverse effects than tricyclic antidepressants, the results of limited clinical studies investigating cardiovascular adverse effects of TRZ are conflicting. 4 It has been noted that TRZ may cause possible cardiovascular adverse effects because of the increased number of cardiotoxicity reports associated with TRZ treatment over the past years. 5,6 Studies have shown that postural hypotension, electrocardiogram (ECG) anomalies (such as prolonged PR interval, long QT syndrome), and cardiac arrhythmias were induced at therapeutic and subtherapeutic doses of TRZ.…”
Section: Introductionmentioning
confidence: 99%